Research on athlete welfare system in China - Wang, Y. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction The athlete welfare work is mainly carried out by various levels of sport administrations and sport associations in China. A support system for athlete development is very essential for athletes to strike a balance between sport and work/education. Methods The methods of literature review, expert interviews and statistical analysis are applied in this research. Face-to-face interviews were conducted with some government officials and athletes. Results The General Administration of Sport of China has issued several guidelines aiming to strengthen athletes` education and career planning. A variety of seminars and training sessions have been organized to help retiring athletes to go through transition period smoothly. In recent years, a lot of investigations into athletes` welfare have been conducted in different provinces and municipalities, and new athlete liaison working groups have been formed to know more about athletes` needs. The Beijing Sport Administration established an information platform for retired athletes in 2019. The Tianjin Sport Administration cooperated with related education departments and social security departments in formulating athlete welfare policies. China Sports Foundation has been providing Disability Mutual Aid Insurance for elite athletes all over the country, and multiple entrepreneurship grants for retired athletes who want to start a business. Discussion To further enhance the support system for athlete development in China, it is suggested that we diversify the development pathways for our athletes and make full use of the athlete welfare departments, so as to care for athletes through the whole process from enrollment into sports teams to retirement. It is also advised that commercial insurances should be offered to athletes as a lifetime guarantee, and new information technology should be utilized more efficiently to facilitate athletes` career transition.